Intrusion Prevention System to Protect Dos Attack - Nurudin, Arif; Mubariq, Ismael (Ann Publisher, 2024)
Data security on a network infrastructure is a very sensitive and vulnerable matter. One alternative to overcome this is to use IPS (Intrusion Prevention System) technology where the technology is a development of IDS (Intrusion Detection System) which uses Snort. In this study, IPS technology is applied using the Untangle Firewall where the Intrusion Prevention feature is available on the platform with the intention of testing the feature on the Untangle Firewall. Testing was carried out using DoS (Denial Of Service) and SSH Brute Force attacks where the Intrusion Prevention feature on the Untangle Firewall can recognize both attacks and can block the attacks using manually added rules.